2017
DOI: 10.1089/ten.tec.2016.0545
|View full text |Cite
|
Sign up to set email alerts
|

A Surgical Device to Study the Efficacy of Bioengineered Skin Substitutes in Mice Wound Healing Models

Abstract: Due to the poor regenerative capacity of adult mammalian skin, there is a need to develop effective skin substitutes for promoting skin regeneration after a severe wound. However, the complexity of skin biology has made it difficult to enable perfect regeneration of skin. Thus, animal models are being used to test potential skin substitutes. Murine models are valuable but their healing process involves dermal contraction. We have developed a device called a dome that is able to eliminate the contraction effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…The mice were divided into four groups (10 mice in each group) and were used to evaluate the biodegradability and biocompatibility of keratin scaffolds on excisional wound on Days 3, 6, 9, and 12. To establish wound models, two full‐thickness excisional wounds (8 mm in size) were created on the back skin using biopsy punch (Chen, Mirza, Kwon, DiPietro, & Koh, ; Jeschke, Sadri, Belo, & Amini‐Nik, ). Mitomycin C (1 mg/ml) was applied to the wound area for 5–10 min to prevent wound healing.…”
Section: Methodsmentioning
confidence: 99%
“…The mice were divided into four groups (10 mice in each group) and were used to evaluate the biodegradability and biocompatibility of keratin scaffolds on excisional wound on Days 3, 6, 9, and 12. To establish wound models, two full‐thickness excisional wounds (8 mm in size) were created on the back skin using biopsy punch (Chen, Mirza, Kwon, DiPietro, & Koh, ; Jeschke, Sadri, Belo, & Amini‐Nik, ). Mitomycin C (1 mg/ml) was applied to the wound area for 5–10 min to prevent wound healing.…”
Section: Methodsmentioning
confidence: 99%
“…The two types of domes used in the study were either perforated or non‐perforated as previously shown (Jeschke et al. ). The domes are used to prevent wound healing in order to test the effects of the grafted skin substitutes alone.…”
Section: Methodsmentioning
confidence: 99%
“…The preparation of wound was performed as previously described (Jeschke et al. ). Briefly, the mice were anesthetized with 1–2% isofluorane + oxygen until unconscious, and the eyes were protected using eye gel.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations